Determinants of International Capital Flows: The Case of Malaysia - Muhammad Asraf, Abdullah; Shazali, Abu Mansor; Puah, Chin Hong (Zant World Press, Australia, 2010)
This paper examines the determinants of international capital inflows into Malaysia in the forms of pull and push factors. The results from Johansen and Juselius cointegration test confirm the existence of a long run stable equilibrium relationship among the variables in the model. In addition, the Error Correction Model (ECM) has been utilized to detect the long run divergence from the equilibrium relationship between the explanatory variables and capital inflows in the specified model. The Wald tests from the ECM further support the notion that real GDP, domestic Treasury bill rate, budget balance, current account balance and US production do Granger cause capital inflows into Malaysia in the short run. The empirical findings in this study show that the pull factors especially budget balance and current account are imperative in explaining inflows of capital into Malaysia. Another interesting finding is the role of real factor as denoted by domestic and industrial country’s outputs in affecting the capital inflows.